Kontrol Kipas Angin Otomatis Berdasarkan Suhu Berbasis Internet of Things (IoT): Penelitian - Dicky Apdilla; Junita Sastri; Annisa Fitriani; Reno Rahmadiansyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The Internet of Things (IoT) is a technology that enables electronic devices to connect and communicate through the internet, allowing systems to operate automatically and efficiently. This study aims to design and implement an IoT-based automatic fan control system based on temperature. The system is designed to address inefficiencies in manual fan operation that is not responsive to real-time temperature changes. The research method used is an experimental approach involving system design, hardware assembly, microcontroller programming, and system testing. The main components include a NodeMCU ESP8266 as the system controller, a DHT22 temperature sensor for detecting ambient temperature, and a relay module to control the fan. The test results show that the system can detect temperature changes in real time and automatically control the fan according to predefined temperature thresholds. In addition, the system can connect to the internet, enabling temperature and fan status monitoring. Therefore, the proposed IoT-based automatic fan control system can improve room comfort and enhance energy efficiency.